BIOLOGICAL ACTIVITIES OF SOME PYRAZOLINE DERIVATIVES - A. GANESH (International Journal of Pharma and Bio Sciences, 2013)
The review of the literature shows that the pyrazoline derivatives is quite stable and has inspired chemists, to utilize pyrazoline fragment in bioactive moieties, to synthesize new pyrazoline derivatives. The past studies of pyrazoline derivative revealed that they are useful in pharmaceutical and agrochemical research. Pyrazoline derivatives display various biological activities such as antitumor, antitubercular, antimicrobial, antibacterial, anti-inflammatory and antioxidant etc.